Diagnosis of timber structures. A case study. - Nunes, L. (2009)
The need to intervene in timber structures is very frequent and especially so in the rehabilitation or conservation of ancient buildings. This paper presents the diagnosis work performed in the future “Wine Museum of Bucelas”, that was subjected in the last years to a total lack of maintenance, the main reason why different biological degradation agents had every condition to increasingly install themselves. The design and maintenance deficiencies of the building roof that led to the present damage level are also presented and related to the degradation problems they cause.